(untitled) (Revista Ciência Agronômica, 2020)
The use of agro-industrial by-products in feeding ruminants has nutritional, environmental and economic advantages, and helps to sustain the production system. The aim of this study was to evaluate the nutritional value of diets containing babassu cake as a substitute for Tifton-85 hay (70, 140, 210, 280 and 350 g kg-1 dry matter: DM). Twenty-five castrated male sheep with a mean body weight of 49.6 ± 9.4 kg were used, distributed in metabolic cages in a completely randomised design. Voluntary intake was obtained from the difference between the amount of feed provided and the leftovers the following morning. To evaluate nutrient digestibility and nitrogen (N) balance, samples of urine and faeces were collected separately. There was no effect on DM intake; however, crude protein (CP) and ether extract intake increased linearly increased linearly. The addition of babassu cake had no effect on DM digestibility (mean value of 604.6 ± 272.8 g kg-1). Apparent CP digestibility and total digestible nutrient content showed increasing linear behaviour, while the digestibility of acid detergent fibre decreased linearly. The level of retained N varied from 9.72 ± 1.12 to 15.51 ± 1.84 g day-1 with the ratio to ingested N ranging from 521.0 ± 26.7 to 578.4 ± 31.8 g kg-1 N. The addition of babassu cake to replace the roughage, increased the nutritional value of the diet. Babassu cake can be included up to a total of 350 g kg-1 DM in the diet as a substitute for Tifton-85 hay.